Overview of Octavius of Mpumalanga and Limpopo Provinces, South Africa (Coleoptera: Staphylinidae: Euaesthetinae) with descriptions of eight new species - Janák, Jiří (Zootaxa, 2025)
Sixteen named species of the genus Octavius Fauvel, 1873 from Mpumalanga and Limpopo Provinces, South Africa were recognised. Eight species are described as new: Octavius barbetonensis Janák, sp. nov., O. hamifer Janák, sp. nov., O. hastifer Janák, sp. nov., O. jaloszynskii Janák, sp. nov., O. klipkraalensis Janák, sp. nov., O. mariepskopensis Janák, sp. nov., O. pinnaculus Janák, sp. nov., and O. woodbushensis Janák, sp. nov. Distribution records of eight species of Octavius are presented, and all species are illustrated. Locality data of two additional unnamed species known only in females are presented.